Current status and advances in adipose-derived stem cells therapy for diabetes mellitus erectile dysfunction - Liu, Jingbang; Jiang, Tao (Frontiers in Medicine, 2025)
Diabetes mellitus erectile dysfunction (DMED) is a severe complication highly prevalent among male diabetic patients, with a global prevalence exceeding 50%, while current therapies exhibit limited efficacy. Adipose-derived stem cells (ADSCs) have emerged as a research focus for DMED treatment due to their accessibility, multipotent differentiation potential and paracrine properties. This article systematically reviews the mechanisms of ADSCs in treating DMED: ADSCs improve cavernous vascularization and endothelial function, inhibit fibrosis and increase smooth muscle content, ameliorate cavernous neuropathy, alleviate programmed cell death in cavernous tissues and reverse phenotypic transformation of cavernous smooth muscle. Additionally, clinical studies on ADSCs therapy for DMED are summarized, along with methods to enhance the efficacy of ADSCs treatment for ED. However, further researches on the underlying mechanisms and clinical trials are needed to advance ADSC from basic research to precision medicine.